Microdetermination of Purine Derivatives with Bromine Monochloride Reagent in Acetic acid Medium - Chauhan, R.P.S.; Agarwal, S.C.; Dwivedi, D.; Dixit, Deepa; Md. Athar Imam, Sd. (Asian Journal of Chemistry, 2010)
In the present work a quick and convenient method had been described for the determination of purine derivatives with the use of bromine monochloride (BrCl) in acetic acid medium at 0–5ºC temperature. The accuracy of the method is within ± 1 %.